Online Physical Education: A Mixed-Methods Study of the Health Perceptions and Professional Effectiveness of Physical Education Teachers - Ben Amotz, Ronit; Green, Gizell; Barak, Sharon; Tesler, Riki; Levi, Sharon; Marques, Adilson; Giladi, Ariela; Joseph, Gili; Ng, Kwok; Zigdon, Avi (MDPI AG, 2025)
The professional efficacy and health perceptions of physical education (PE) teachers, along with school characteristics, significantly impact their ability to navigate remote teaching challenges, maintain student engagement, and deliver inclusive, effective instruction. Remote teaching has become a widespread instructional method, particularly during the COVID-19 pandemic, but it also presents unique challenges for PE educators, requiring specialized pedagogical strategies and technological adaptation. This study aims to evaluate the professional efficacy, health perceptions, and pedagogical approaches of PE teachers in the context of remote teaching. Employing an explanatory sequential mixed-methods design, we conducted a cross-sectional web survey (N = 757) followed by in-depth interviews (N = 15). Participants were selected from a list provided by the Israeli Ministry of Education, with inclusion criteria requiring at least one year of PE teaching experience. Quantitative data analysis included chi-square tests, t-tests, Pearson correlation, and multiple regression analyses, while qualitative data were analyzed using conventional content analysis to identify emergent themes. Our analysis reveals that female with higher levels of education, research skills, and advanced knowledge in teaching technologies exhibit significantly greater teaching professional efficacy in remote settings. These findings suggest that educational institutions should develop tailored training programs that account for gender and educational differences, thereby equipping PE teachers with the necessary skills to excel in remote teaching environments. This proactive approach will better prepare PE educators to navigate future challenges in the ever-evolving landscape of education.